Effects of nightmares on the cortisol awakening response: An ambulatory assessment pilot study - Hess, Gabriela; Schredl, Michael; Gierens, Andrea; Domes, Gregor (Psychoneuroendocrinology, 2020)
Previous studies have reported an association between sleep-related factors such as sleep duration, sleep quality and time of awakening with the cortisol awakening response (CAR). Preliminary evidence suggests that frequent nightmares are associated with a blunted CAR. In the present pilot study we investigated the effect of acute nightmares on the CAR and the cortisol profile of the subsequent day using a within-subject ambulatory assessment study design. Thirty healthy volunteers who reported frequent nightmares enrolled in the study. Over a period of 14 days, salivary samples in addition to sleep-related and state variables were collected at home over the day. Salivary profiles of free cortisol and alpha amylase for up to two days following a nightmare were compared to those following a neutral dream. Overall, mood and health were decreased and the CAR was elevated following nightmares compared to neutral dreams. No differences were found for alpha amylase and for all variables over the remaining part of the day. Results suggest that sleep-related factors such as the occurrence of nightmares account for a certain amount of variance observed in the CAR. This has important methodological implications for CAR studies in general and might have even more relevance for studies in clinical populations suffering from chronic sleep disturbances.
Gesehen am 12.02.2024